Pengaruh Pertumbuhan Ekonomi, Investasi, dan Belanja Modal terhadap Kesejahteraan Masyarakat di Jawa Tengah Tahun 2012 – 2018 - An Nisa An Nisa; Herniwati Retno Handayani (Universitas Diponegoro, 2021)
Social walfare is one of the main goal of developing area to achieve a better life. The improvement of social walfare can't be separated from economic activities that is done by all kinds of society, from private area and government area. The purpose of this study was to examine the effect of economic growth, domestic investment, foreign investment, and capital expenditure on social walfare at 2012-2018 in Central Java Province. This study uses secondary data with cross-section data depends on 29 districts and 6 cities in Central Java Province and time-series data from 2012- 2018. The analytical tool used in estimating the research model is panel data regression with Fixed Effect Model. The result study is simultaneously, independent variable has an effect to dependent variable. Meanwhile partially, the variable of domestic investment and capital expenditure have significant effect to social welfare while economic growth and foreign investment have no significant effect to the social walfare in Central Java Province.